2020
DOI: 10.1021/acs.jpcb.0c00574
|View full text |Cite
|
Sign up to set email alerts
|

Tau R3–R4 Domain Dimer of the Wild Type and Phosphorylated Ser356 Sequences. I. In Solution by Atomistic Simulations

Abstract: In Alzheimer’s disease, neurofibrillary lesions correlate with cognitive deficits and consist of inclusions of tau protein with cross-β structure. A stable dimeric form of soluble tau has been evidenced in the cells, but its high-resolution structure is missing in solution. We know, however, that cryo-electron microscopy (c-EM) of full-length tau in the brain of an individual with AD displays a core of eight β-sheets with a C-shaped architecture spanning the R3–R4 repeat domain, while the rest of the protein i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(57 citation statements)
references
References 69 publications
5
52
0
Order By: Relevance
“…The Tau43 domain in the solution NMR htau40 investigation has increased β‐sheet propensity, 13 also recent reports show β‐populated domains in different diseased Tau isoforms 57,58 . However, Tau43 structural ensemble, within currently simulated timescales, are intrinsically unstructured with transient structural propensity, in qualitative agreement with several studies, 11,28,34,59–61 where relatively compact, transiently structured, yet disordered conformations have been predicted for monomeric and oligomeric conformational ensembles of Tau isoforms. Together, these indicate the current monomeric conformational ensemble to be a relatively compact yet unstructured metastable state in the early aggregation process of Tau43, which will be further underscored with corresponding insights from structural parameters.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The Tau43 domain in the solution NMR htau40 investigation has increased β‐sheet propensity, 13 also recent reports show β‐populated domains in different diseased Tau isoforms 57,58 . However, Tau43 structural ensemble, within currently simulated timescales, are intrinsically unstructured with transient structural propensity, in qualitative agreement with several studies, 11,28,34,59–61 where relatively compact, transiently structured, yet disordered conformations have been predicted for monomeric and oligomeric conformational ensembles of Tau isoforms. Together, these indicate the current monomeric conformational ensemble to be a relatively compact yet unstructured metastable state in the early aggregation process of Tau43, which will be further underscored with corresponding insights from structural parameters.…”
Section: Resultssupporting
confidence: 80%
“…In recent times, molecular dynamics (MD) simulations (often in conjunction with experiments) have significantly contributed in knowing the unknown aspects of Tau 24–35 . The PHF6 has been found to be stronger in aggregation propensity over PHF6* ( 275 VQIINK 280 , another PHF forming segment in hTau40), 24,32 and corresponding stability of the oligomers were controlled by hydrophobic and polar interactions 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Phosphorylation of Ser356 has been shown experimentally to block tau interactions with Aβ peptide (Guo et al, 2006) and inhibits the seeding activity of the K18 tau construct in the presence of heparin (Haj-Yahya et al, 2020). Meanwhile, REMD simulations of the PHF dimer show that pSer356 modifies the conformational ensemble of a tau dimer in solution (Derreumaux et al, 2020). It has been suggested that pSer356 may lead to increased sampling of extended conformations of disordered tau, thereby exposing residues to the fibril template during binding (Popov et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…All-atom replica exchange MD (REMD) simulations (Larini et al, 2013;Ganguly et al, 2015;Levine et al, 2015) and coarse-grained (Smit et al, 2017) simulations of important nucleating fragments of tau have provided information about the early stages of tau aggregation and which factors stabilize either parallel or antiparallel β-sheet structures (Ganguly et al, 2015). REMD simulations performed by Derreumaux et al of the R3-R4 domain dimer identified elongated, U-shaped, V-shaped, and globular configurations, but not the C-shaped structure characteristic of AD NFTs (Derreumaux et al, 2020). Recent steered molecular dynamics (SMD) simulations assessed the stability and dissociation of tau from an isolated protofibril pentamer, suggesting that the PHF and SF protofibrils induce a different pathway for misfolding of tau (Liu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The central proline-rich region serves for intermolecular interactions such as SH3-containing proteins and peptidyl-prolyl cis/trans isomerase, whereas the N-terminal moiety projects out of the microtubule bundle to interact with other cytoskeletal elements and membranes. This domain is composed of two repeats of 29 amino acids, termed N1 and N2 [158,159]. Alternative splicing gives rise to six tau isoforms, differing in the amount of N-terminal repeats (0N, 1N or 2N) and the inclusion of the C-terminal repeat R2 (producing 3R and 4R tau isoforms) [157,158].…”
Section: Tau and Tauopathiesmentioning
confidence: 99%